1999
DOI: 10.1152/jappl.1999.87.1.269
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic localization of 24- and 96-h particle retention in canine airways

Abstract: Long-term retention of particles in airways is controversial. However, precise anatomic localization of the particles is not possible in people. In this study the anatomic location of retained particles after shallow bolus inhalation was determined in anesthetized, ventilated beagle dogs. Fifty 30-cm(3) boluses containing monodisperse 2.5-micron polystyrene particles (PSL) were delivered to a shallow lung depth of 81-129 cm(3). At 96 h before euthanasia, red fluorescent PSL were used; at 24 h, green fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 48 publications
3
33
1
1
Order By: Relevance
“…The rst interpretation is in agreement with earlier results with the extremely slow inhalation technique [ 15] and predictions with the USBG model for particle deposition in the lung. This interpretation is also in agreement with a study using shallow bolus inhalations in dogs by Kreyling et al [ 35] , who found considerable fractions of particles deposited in both the bronchiolar and the alveolar regions. In this experiment, volumetric lung depth varied between 40 and 100 ml, which represented 45% to 85% of the volume of the airways with no alveoli ( phase I ).…”
Section: Discussionsupporting
confidence: 93%
“…The rst interpretation is in agreement with earlier results with the extremely slow inhalation technique [ 15] and predictions with the USBG model for particle deposition in the lung. This interpretation is also in agreement with a study using shallow bolus inhalations in dogs by Kreyling et al [ 35] , who found considerable fractions of particles deposited in both the bronchiolar and the alveolar regions. In this experiment, volumetric lung depth varied between 40 and 100 ml, which represented 45% to 85% of the volume of the airways with no alveoli ( phase I ).…”
Section: Discussionsupporting
confidence: 93%
“…Gamma scintigraphy is the most commonly used imaging method but single photon emission computed tomography (SPECT) and positron emission tomography (PET) are growing in popularity [149,150]. In general terms two major approaches have been adopted for imaging small animals: the first is the adaptation of clinical imaging technologies such as gamma scintigraphy, SPECT (Figure 4) [151] and PET to the smaller animal dimensions and the second is based on new evolving technologies based on whole-body photonic imaging [152].…”
Section: Imaging Of Drug Deposition and Absorptionmentioning
confidence: 99%
“…A number of studies have used nuclear imaging to image radiolabelled drugs and particles delivered to small [153] and more commonly large [154,151,155158] animals.…”
Section: Imaging Of Drug Deposition and Absorptionmentioning
confidence: 99%
“…This apparent difference between rodents and man in the retention time of particles in airways and hence their clearance from this lung compartment has to be utterly considered when extrapolating rodent data to man. The prolonged retention of MP was also observed in the airways of dogs (Kreyling et al 1999). As mentioned already in the previous paragraph, the mechanisms for prolonged retention and, hence, delayed clearance of particles from airways as observed in humans and dogs remain unclear.…”
Section: Airwaysmentioning
confidence: 54%